Clinical and molecular characteristics of estrogen receptor‐positive ultralow risk breast cancer tumors identified by the 70‐gene signature. Issue 12 (7th March 2022) - Johansson, Annelie; Yu, Nancy Y.; Iftimi, Adina; Tobin, Nicholas P.; van 't Veer, Laura; Nordenskjöld, Bo; Benz, Christopher C.; Fornander, Tommy; Perez‐Tenorio, Gizeh; Stål, Olle; Esserman, Laura J.; Yau, Christina; et al.
Abstract: The metastatic potential of estrogen receptor (ER)‐positive breast cancers is heterogeneous and distant recurrences occur months to decades after primary diagnosis. We have previously shown that patients with tumors classified as ultralow risk by the 70‐gene signature have a minimal long‐term risk of fatal breast cancer. Here, we evaluate the previously unexplored underlying clinical and molecular characteristics of ultralow risk tumors in 538 ER‐positive patients from the Stockholm tamoxifen randomized trial (STO‐3). Out of the 98 ultralow risk tumors, 89% were luminal A molecular subtype, whereas 26% of luminal A tumors were of ultralow risk. Compared to other ER‐positive tumors, ultralow risk tumors were significantly (Fisher's test, P  < .05) more likely to be of smaller tumor size, lower grade, progesterone receptor (PR)‐positive, human epidermal growth factor 2 (HER2)‐negative and have low Ki‐67 levels (proliferation‐marker). Moreover, ultralow risk tumors showed significantly lower expression scores of multi‐gene modules associated with the AKT/mTOR‐pathway, proliferation (AURKA), HER2/ ERBB2‐ signaling, IGF1‐pathway, PTEN‐loss and immune response (IMMUNE1 and IMMUNE2) and higher expression scores of the PIK3CA‐mutation‐associated module. Furthermore, 706 genes were significantly (FDR < 0.001) differentially expressed in ultralow risk tumors, including lower expression of genes involved in immune response, PI3K/Akt/mTOR‐pathway, histones, cell cycle, DNA repair, apoptosis and higher expression of genes coding for epithelial‐to‐mesenchymal transition and homeobox proteins, among others. In conclusion, ultralow risk tumors, associated with minimal long‐term risk of fatal disease, differ from other ER‐positive tumors, including luminal A molecular subtype tumors. Identification of these characteristics is important to improve our prediction of nonfatal vs fatal breast cancer. Abstract : What's new? The metastatic potential of estrogen receptor (ER)‐positive breast cancers is heterogeneous, and distant recurrences may occur months to decades after primary diagnosis. However, the long‐term risk of metastatic disease in breast cancer remains largely unexplored. Using a previously‐established 70‐gene signature to identify breast cancer patients with minimal long‐term risk of fatal disease, here the authors show that ultralow‐risk tumors differ from other ER‐positive breast cancer tumors, including luminal molecular subtype tumors. Differences were found in both clinical breast cancer markers and molecular features. These results are important for the characterization and prediction of non‐fatal vs fatal breast cancer.